Efektifitas Model Quantum Teaching Terhadap Pembelajaran Matematika Siswa di Sekolah Dasar - Nursalam, Muhammad; HS, Eka Fitriana; Jusmawati, Jusmawati (Universitas Pahlawan Tuanku Tambusai, 2021)
This research stems from the difficulty of students of SDN Salupompong, Mamuju Regency, West Sulawesi in following the learning process, this is due to the lack of development of teaching models and methods by teachers which impact on relatively low student learning outcomes. Therefore, this study aims to determine the effectiveness of the Quantum Teaching model in class IV SDN Salupompong, Mamuju Regency, West Sulawesi. This study used an experimental research method with descriptive analysis and imperative analysis carried out with four learning meetings and two test meetings. The learning outcomes obtained were 3,7, student activity was 3,53, and student response was 3,44, from the three indicators of the effectiveness of the Quantum Teaching learning model, it can be obtained an average effectiveness of 3,55 with the very effective category.